Winemaking procedures and their influence on wine stabilization: Effect on the chemical profile - De Castilhos, Maurício Bonatto Machado [UNESP]; Del Bianchi, Vanildo Luiz [UNESP] (My University, 2016)
Wine plays an important role in the group of alcoholic beverages due to the health benefits provided by its daily intake, since it presents phenolic compounds that help to prevent or avoid some particular diseases. These substances are closely related to the intrinsic features of the grape cultivar as well as the winemaking process and its variations determine their concentration. Within this context, as wine technology is complex and involves several steps, wineries usually face problems of degradation of these compounds during the winemaking process, which negatively influence the wine quality. Wine quality is closely related to its chemical profile, mainly phenolic composition and proanthocyanidin content, due to their relationship with antioxidant capacity and wine aging potential, both closely related to wine stability. In contrast, wineries use several stabilization techniques such as filtration, fining, tartrate and protein stabilization, which could negatively affect the wine phenolic composition and its antioxidant capacity, as well as its stability. The transformation of the grape in wine demands intensive care as it involves great number of chemical reactions and could explain the formation of new pigments or compounds by the enzymatic or non-enzymatic reactions, which can be resulted from the variations in the winemaking process. Despite the aforementioned classical stabilization processes applied during the winemaking, the drying process (natural or controlled) has been the subject of studies, since it provides the formation of some compounds that alter the phenolic composition and improve the antioxidant capacity. Furthermore, the grape pre-dehydration can degrade the phenolic compounds by the use of the heat and enhance the phenolic compounds extraction as a result of the irreversible damage caused on the grape skin by the use of the heat. In addition, the application of the submerged cap is another alternative technique aiming stabilizes the wine color providing the improvement of the anthocyanins extraction from to the berries to the juice during the alcoholic fermentation. In addition, other winemaking procedures such as carbonic maceration, cold soaking and cold maceration provide changes on the phenolic content and, consequently, on wine stability. Thus, this chapter aims to present a discussion about the variation in winemaking as an alternative to wine stabilization and their influence on the chemical profile, mainly on the increase or decrease of the phenolic compounds, since they are responsible for important sensory features, nutritional effects and wine stability.
Keywords: Chemical profile; Phenolic compounds; Wine; Wine stability; Winemaking